Native trees are related to advanced bird breeding phenology and increased reproductive success along an urban gradient - Claire J. Branston; Pablo Capilla‐Lasheras; Conor Haugh; Paul J. Baker; Rachel Reid; Kate Griffiths; Stewart White; Davide M. Dominoni (Ecology, 2026)
Urban areas are altered from natural landscapes in several ways that can impact wildlife. Birds are widespread in urban areas, and it is well documented that there are phenotypic differences between urban and non‐urban conspecifics. However, little is known about which characteristics of the urban environment are driving differences. We used 9 years of data from nest boxes spread across 20 sites along a 40‐km urban–non‐urban gradient in Scotland to test whether characteristics of the urban environment (native, non‐native, native oak ( Quercus spp.), birch ( Betula spp.) foliage availability, temperature and human population density, and the interaction between foliage and temperature) influenced phenology and reproductive success in blue tits ( Cyanistes caeruleus ). We found that higher foliage availability of native foliage, and specifically of the most common native genus, oak, was associated at the territory level with earlier first egg laying date. Higher non‐native foliage availability at both a site and territory level was negatively related to clutch size. The number of fledglings produced was reduced at sites with higher levels of non‐native foliage and increased at sites with greater amounts of native oak foliage present. We also found territories with a higher human population density had reduced fledging success. Temperature was negatively related to first egg laying date, clutch size and the number of fledglings produced. Moreover, the number of Lepidopteran larvae, blue tits' preferred prey, that were collected over the breeding season was positively related to native oak foliage availability. Our results strongly indicate that the presence of native trees, such as oak, are beneficial to breeding insectivores by increasing the number of fledglings they can successfully raise, likely due to the increased availability of invertebrate prey. We suggest that urban planting regimes should be carefully considered, selecting tree species that are native or non‐native congeneric species, and most importantly that will host Lepidoptera larvae. This will not only help to support complete food chains, but also to maximize biodiversity and ecosystem services of urban green spaces.

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

Hidden Causes of Variation in Offspring Reproductive Value: Negative Effects of Maternal Breeding Age on Offspring Telomere Length Persist Undiminished Across Multiple Generations - Valeria Marasco; Winnie Boner; Kate Griffiths; Shirley Raveh; Pat Monaghan (Ecology Letters, 2025)
Offspring of older breeders frequently show reduced longevity, which has been linked to shorter offspring telomere length. It is currently unknown whether such telomere reduction persists beyond a single generation, as would be the case if germline transmission is involved. In a within‐grandmother, multi‐generational study using zebra finches, we show that the shorter telomeres observed in F1 offspring of older mothers are still present in the F2 generation even when the breeding age of their F1 mothers is young. The effect was substantial: 43% shorter telomeres in grandoffspring from the ‘grandmother old at breeding’ line compared with those from the ‘grandmother young at breeding’ line. Shorter telomeres at fledging in this species are associated with a reduction in lifespan. Our data demonstrate the need to look beyond a single generation to explain inter‐individual variation in ageing rates and thereby variation in optimal allocation of age‐specific reproductive effort.

Urbanisation weakens selection on the timing of breeding and clutch size in blue tits but not in great tits - Claire J. Branston; Pablo Capilla-Lasheras; Christopher J. Pollock; Kate Griffiths; Stewart White; Davide M. Dominoni (Behavioral Ecology and Sociobiology, 2021)
Urbanisation is a globally occurring phenomenon and is predicted to continue increasing rapidly. Urban ecosystems present novel environments and challenges which species must acclimate or adapt to. These novel challenges alter existing or create new selection pressures on behaviours which provide an opportunity to investigate eco-evolutionary responses to contemporary environmental change. We used 7 years of breeding data from urban and forest populations of blue and great tits to understand whether selection for timing of breeding or clutch size differed between the two habitats and species. We found that urban great tits laid eggs earlier than their forest counterparts, but there was no evidence of a difference in selection for earlier breeding. Blue tits, however, did not differ in timing of egg laying between the two habitats, but selection for earlier laying was weaker in the urban environment. Both species laid smaller clutches in the urban site and had positive selection for larger clutch sizes which did not differ in strength for the great tits but did for blue tits, with weaker selection in the urban population. Our results suggest that food availability for nestlings may be constraining urban birds, and that the temporal cues females use to time breeding correctly, such as tree budburst and food availability, may be absent or reduced in urban areas due to lower caterpillar availability. These results have implications for our understanding of the adaptation of wild animals to city life. Significance statement Urbanisation is expanding rapidly and changing the environment many species live in. A key challenge is to understand how species adapt to the urban environment, why some species can adapt, why others cannot and what we can do to ensure that cities are ecologically sustainable and biodiversity rich. Here we show that the strength of natural selection for early breeding and larger clutch size is weaker in urban than non-urban blue tits, likely due to reduced and irregular availability of natural insect food in urban areas. This effect was not found in great tits. Thus, urbanisation can alter the selection pressures wild animals are exposed to, but this effect may differ between species, even when closely related. This has implications for our understanding of how species adapt to urban life.

Comparison of Unyvero P55 Pneumonia Cartridge, in-house PCR and culture for the identification of respiratory pathogens and antibiotic resistance in bronchoalveolar lavage fluids in the critical care setting - Naomi J. Gadsby; Martin P. McHugh; Callum Forbes; Laura MacKenzie; Stephen K. D. Hamilton; David M. Griffith; Kate E. Templeton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Telomere length measurement by qPCR in birds is affected by storage method of blood samples - Sophie Reichert; Hannah Froy; Winnie Boner; Theresa M. Burg; Francis Daunt; Robert Gillespie; Kate Griffiths; Sue Lewis; Richard A. Phillips; Dan H. Nussey; Pat Monaghan (Oecologia, 2017)

Maximizing the phylogenetic diversity of seed banks - Kate E. Griffiths; Sharon T. Balding; John B. Dickie; Gwilym P. Lewis; Tim R. Pearce; Richard Grenyer (Conservation Biology, 2015)
Ex situ conservation efforts such as those of zoos, botanical gardens, and seed banks will form a vital complement to in situ conservation actions over the coming decades. It is therefore necessary to pay the same attention to the biological diversity represented in ex situ conservation facilities as is often paid to protected‐area networks. Building the phylogenetic diversity of ex situ collections will strengthen our capacity to respond to biodiversity loss. Since 2000, the Millennium Seed Bank Partnership has banked seed from 14% of the world's plant species. We assessed the taxonomic, geographic, and phylogenetic diversity of the Millennium Seed Bank collection of legumes (Leguminosae). We compared the collection with all known legume genera, their known geographic range (at country and regional levels), and a genus‐level phylogeny of the legume family constructed for this study. Over half the phylogenetic diversity of legumes at the genus level was represented in the Millennium Seed Bank. However, pragmatic prioritization of species of economic importance and endangerment has led to the banking of a less‐than‐optimal phylogenetic diversity and prioritization of range‐restricted species risks an underdispersed collection. The current state of the phylogenetic diversity of legumes in the Millennium Seed Bank could be substantially improved through the strategic banking of relatively few additional taxa. Our method draws on tools that are widely applied to in situ conservation planning, and it can be used to evaluate and improve the phylogenetic diversity of ex situ collections. Maximizar la Riqueza Filogenética de los Bancos de Semillas

Vegetation exerts a greater control on litter decomposition than climate warming in peatlands - Susan E. Ward; Kate H. Orwin; Nicholas J. Ostle; Maria J. I. Briones; Bruce C. Thomson; Robert I. Griffiths; Simon Oakley; Helen Quirk; Richard D. Bardgett (Ecology, 2015)
Historically, slow decomposition rates have resulted in the accumulation of large amounts of carbon in northern peatlands. Both climate warming and vegetation change can alter rates of decomposition, and hence affect rates of atmospheric CO 2 exchange, with consequences for climate change feedbacks. Although warming and vegetation change are happening concurrently, little is known about their relative and interactive effects on decomposition processes. To test the effects of warming and vegetation change on decomposition rates, we placed litter of three dominant species ( Calluna vulgaris , Eriophorum vaginatum , Hypnum jutlandicum ) into a peatland field experiment that combined warming with plant functional group removals, and measured mass loss over two years. To identify potential mechanisms behind effects, we also measured nutrient cycling and soil biota. We found that plant functional group removals exerted a stronger control over short‐term litter decomposition than did ~1°C warming, and that the plant removal effect depended on litter species identity. Specifically, rates of litter decomposition were faster when shrubs were removed from the plant community, and these effects were strongest for graminoid and bryophyte litter. Plant functional group removals also had strong effects on soil biota and nutrient cycling associated with decomposition, whereby shrub removal had cascading effects on soil fungal community composition, increased enchytraeid abundance, and increased rates of N mineralization. Our findings demonstrate that, in addition to litter quality, changes in vegetation composition play a significant role in regulating short‐term litter decomposition and belowground communities in peatland, and that these impacts can be greater than moderate warming effects. Our findings, albeit from a relatively short‐term study, highlight the need to consider both vegetation change and its impacts below ground alongside climatic effects when predicting future decomposition rates and carbon storage in peatlands.

Improving the assessment and valuation of climate change impacts for policy and regulatory analysis - Alex L. Marten; Robert E. Kopp; Kate C. Shouse; Charles W. Griffiths; Elke L. Hodson; Elizabeth Kopits; Bryan K. Mignone; Chris Moore; Steve C. Newbold; Stephanie Waldhoff; Ann Wolverton (Climatic Change, 2013)

Sex-biased incidental mortality of albatrosses and petrels in longline fisheries: differential distributions at sea or differential access to baits mediated by sexual size dimorphism? - Leandro Bugoni; Kate Griffiths; Robert W. Furness (Journal of Ornithology, 2011)

Are European starlings breeding in the Azores archipelago genetically distinct from birds breeding in mainland Europe? - Verónica C. Neves; Kate Griffiths; Fiona R. Savory; Robert W. Furness; Barbara K. Mable (European Journal of Wildlife Research, 2010)

Is sex-specific mass gain in Cory’s shearwaters Calonectris diomedea related to begging and steroid hormone expression? - Petra Quillfeldt; Inga Träger; Kate Griffiths; Katherine L. Buchanan; Juan F. Masello (Behavioral Ecology and Sociobiology, 2007)

Thermophilic bacterial DNA polymerases with reverse-transcriptase activity - Kate Griffiths; Harini Shandilya; Elizabeth K. Flynn; Mekbib Astatke; Po-Jen Shih; Jun E. Lee; Gary F. Gerard; Moreland D. Gibbs; Peter L. Bergquist (Extremophiles, 2004)

Primary sex ratios in birds: problems with molecular sex identification of undeveloped eggs - Kathryn E. Arnold; Kate J. Orr; Richard Griffiths (Molecular Ecology, 2003)
Sex allocation studies seek to ascertain whether mothers manipulate offspring sex ratio prior to ovulation. To do so, DNA for molecular sexing should be collected as soon after conception as possible, but instead neonates are usually sampled. Here, we aim to identify and quantify some of the problems associated with using molecular techniques to identify the sex of newly laid avian eggs. From both fertilized and unfertilized chicken ( Gallus gallus ) eggs, we sampled (1) the blastoderm/disc, (2) vitelline membrane and (3) a mixture of (1) and (2). Thus, we replicated scenarios under which contaminated samples are taken and/or unfertilized eggs are not identified as such and are sampled. We found that two commonly used molecular sexing tests, based on the CHD‐1 genes, differed in sensitivity, but this did not always predict their ability to sex egg samples. The vitelline membrane was a considerable source of maternal and probably paternal contamination. Fertile eggs were regularly assigned the wrong sex when vitelline membrane contaminated the blastoderm sample. The membrane of unfertilized eggs was always female, i.e. maternal DNA had been amplified. DNA was amplified from 47 to 63% of unfertilized blastodiscs, even though it was highly unlikely that DNA from a single haploid cell could be amplified reliably using these polymerase chain reaction (PCR) techniques. Surprisingly, the blastodiscs were identified as both males and females. We suggest that in these cases only maternal DNA was amplified, and that ‘false’ males, Z not ZZ, were detected. This was due to the reduced ability of both sets of primers to anneal to the W chromosome compared to the Z chromosome at low DNA concentrations. Overall, our data suggested that estimates of primary sex ratios based on newly laid eggs will be appreciably inaccurate.

The use of amplified fragment length polymorphism (AFLP) in the isolation of sex‐specific markers - RICHARD Griffiths; KATE Orr (Molecular Ecology, 1999)
Sex identification is a problem in research and conservation. It can often be solved using a DNA test but this is only an option if a sex‐specific marker is available. Such markers can be identified using the amplified fragment length polymorphism (AFLP) technique. This is usually a taxonomic method, as it produces a DNA fingerprint of 50–100 PCR bands. However, if male and female AFLP products are compared, sex‐specific markers are confined to the heterogametic sex and can rapidly be identified. Once a marker is found, AFLP can be used to sex organisms directly or the marker can be sequenced and a standard PCR test designed.

A DNA test to sex most birds - RICHARD GRIFFITHS; MIKE C. DOUBLE; KATE ORR; ROBERT J. G. DAWSON (Molecular Ecology, 1998)
Birds are difficult to sex. Nestlings rarely show sex‐linked morphology and we estimate that adult females appear identical to males in over 50% of the world's bird species. This problem can hinder both evolutionary studies and human‐assisted breeding of birds. DNA‐based sex identification provides a solution. We describe a test based on two conserved CHD (chromo‐helicase‐DNA‐binding) genes that are located on the avian sex chromosomes of all birds, with the possible exception of the ratites (ostriches, etc.; Struthioniformes). The CHD‐W gene is located on the W chromosome; therefore it is unique to females. The other gene, CHD‐Z, is found on the Z chromosome and therefore occurs in both sexes (female, ZW; male, ZZ). The test employs PCR with a single set of primers. It amplifies homologous sections of both genes and incorporates introns whose lengths usually differ. When examined on a gel there is a single CHD‐Z band in males but females have a second, distinctive CHD‐W band.